Special Issue: Editorial Comment - Boylan, Colin (Australian and International Journal of Rural Education, 2009)
As SPERA celebrates its 25th year as the national organisation whose voice on rural and remote education and training in Australia, the Executive determined mark this historical milestone with a number of significant events. The 2009 annual national conference with its theme Education in a Digital Present: Enriching Rural Communities continues to explore innovative and creative ways of providing education to students located in rural and remote places. During the 25th Conference, the roles, purposes and impacts of digital information technologies will be explored as they transform the way we work, learn and communicate. In this digital revolution, educators, parents and systems are engaged in a comprehensive search for strategies and tools for effective online/digital teaching based on the principles of learning as a social process and engaging the advantages of new technologies to support e-learning decision-making, instructional choices, program and course planning and the delivery of curricula.